Evaluation of off-service rotations at National Guard Health Affairs: Results from a perception survey of off-service residents - Mustafa M Alquraini; Lubna Baig; Mohi Magzoub; Amir Omair (Wolters Kluwer Medknow Publications, 2013)
Context: "Off-service" clinical rotations are part of the necessary requirements for many residency training programs. Because these rotations are off-service, little attention is given to their structure and quality of training. This often leads to suboptimal educational experience for the residents on these rotations. Aims: The aim of this study was to assess medical residents' perceptions, opinions, and levels of satisfaction with their "off-service" rotations at a major residency training site in Saudi Arabia. It was also to evaluate the reliability and validity of a questionnaire used for quality assurance in these rotations. Improved reliability and validity of this questionnaire may help to improve the educational experience of residents in their "off-service" rotations. Materials and Methods: A close-ended questionnaire was developed, Pilot tested and distributed to 110 off-service residents in training programs of different specializations at King Fahad Naitonal Guard Hospital and King Abdulziz Medical City, Riyadh, Saudi Arabia, between September 2011 and December 2011. Results: A total of 80 out of 110 residents completed and returned the questionnaire. Only 33% of these residents had a clear set of goals and educational learning objectives before the beginning of their off-service rotations to direct their training. Surgical specializations had low satisfaction mean scores of 57.2 (11.9) compared to emergency medicine, which had 70.7 (16.2), P value (0.03). The reliability of the questionnaire was Cronbach's alpha 0.57. The factor analysis yielded a 4-factor solution (educational environment, educational balance, educational goals and objectives, and learning ability); thus, accounting for 51% variance in the data. Conclusion: Our data suggest that there were significant weaknesses in the curriculum for off-service clinical rotations in KAMC and that residents were not completely satisfied with their training.